Inovasi Teknologi dan Transformasi Ekonomi: Peran Kewirausahaan dalam Pembangunan Ekonomi Daerah - Putri Safa Aulia Lubis; Sefianza Suhana Sinaga (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research aims to investigate how technological innovation influences economic transformation at the regional level, with a specific focus on the role of entrepreneurship in the economic development process. The methodology involves surveys conducted within local entrepreneurial sectors and the implementation of cutting-edge technology across various economic regions. The findings indicate that the adoption of technological innovations, combined with a strong entrepreneurial presence, has a positive impact on enhancing regional economic competitiveness, expanding employment opportunities, and significantly driving sustainable economic growth. This underscores the importance of collaboration between technological innovation and the role of entrepreneurship in designing effective strategies for local economic development.